Maternal vs Fetal Origin of Placental Intervillous Thrombi. Issue 3 (21st September 2021) - Sukhanova, Madina; Mithal, Leena B; Otero, Sebastian; Azad, Hooman A; Miller, Emily S; Jennings, Lawrence J; Shanes, Elisheva D; Goldstein, Jeffery A
Abstract: Objectives: To determine maternal vs fetal origin for blood in placental intervillous thrombi (IVTs). Methods: We used comparative analysis of microsatellites (short tandem repeats [STRs]), sex chromosome fluorescence in situ hybridization (FISH), and immunohistochemistry (IHC) for fetal (ɑ-fetoprotein [AFP]) and maternal (immunoglobulin M [IgM]) serum proteins to distinguish the origin of IVTs. Using an informatics approach, we tested the association between IVTs and fetomaternal hemorrhage (FMH). Results: In 9 of 10 cases, the preponderance of evidence showed that the thrombus was mostly or entirely maternal in origin. In 1 case, the thrombus was of mixed origins. STR testing was prone to contamination by entrapped fetal villi. FISH was useful but limited only to cases with male fetuses. IgM showed stronger staining than AFP in 9 cases, supporting maternal origin. By informatics, we found no association between IVTs and FMH. Conclusions: Evidence supports a maternal origin for blood in IVTs. IHC for IgM and AFP may be clinically useful in determining maternal vs fetal contribution to IVTs.